2021
DOI: 10.1007/s10566-021-09652-y
|View full text |Cite
|
Sign up to set email alerts
|

Thought Problems and Aggression Over Time Among Youth in Foster Care

Abstract: Background Youth in foster care may demonstrate high levels of aggression and thought problems. There is a growing trend to consider mental health symptoms of youth involved with the foster care system from a developmental trauma perspective. Objective The aim of this study was to test if trauma, race, age, and gender predicted variability in thought problems and aggression for youth in foster care. Method The sample ( n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…This scale has been established as a good first-step screening measure to detect prodromic signs of psychotic disorders [ 50 ]. As it is composed of only 7 items, this scale has often shown Cronbach’s alpha values lower than 0.70 [ 51 , 52 ]. In this study, Cronbach’s alpha was 0.67, and there was good item inter-correlation (all values > 0.30, p < 0.000), indicating acceptable reliability for a scale composed of few items [ 53 , 54 , 55 ].…”
Section: Methodsmentioning
confidence: 99%
“…This scale has been established as a good first-step screening measure to detect prodromic signs of psychotic disorders [ 50 ]. As it is composed of only 7 items, this scale has often shown Cronbach’s alpha values lower than 0.70 [ 51 , 52 ]. In this study, Cronbach’s alpha was 0.67, and there was good item inter-correlation (all values > 0.30, p < 0.000), indicating acceptable reliability for a scale composed of few items [ 53 , 54 , 55 ].…”
Section: Methodsmentioning
confidence: 99%
“…In a study that examined thought problems and aggression among children in out-of-home care, Farley et al (2022 , p. 795) found that placement in care institutions provided a structure that reduced the incidence of aggression in children. This strengthens the view that children require structure and a measure of predictability in their lives to develop normatively ( Varelas et al, 2015 , p. 517).…”
Section: Introductionmentioning
confidence: 99%